EVALUATION OF EGG SHELL MICROSTRUCTURE PASCA FORMULATION OF KHITOSAN LIQUID SMOKE IN POST TIME SALTING - MIWADA I N. S.; M. HARTAWAN; I K. SUKADA (Majalah Ilmiah Peternakan, 2018)
This study aims at analyzing the ability of chitosan-formula liquid smoke to make innovation of curing timeswith penetration through the pores of duckling egg shells on the process of salting. A completely randomized design(CRD) was used with long curing treatment in 5, 10, 15, and 20 days. Besides, formula chitosan-liquid smoke with20 g/l and 3% concentration were used in this experiment. The results showed that the curing of time up to 15 daysgave the highest score (P<0.05) with good criteria. The quality of chemical in a long curing times gave significantdifferences (P<0.05) from indicators as of pH value, protein, and content of total phenol, and acids. The resultof SEM (Scanning Electron Microscope) showed that formulation of chitosan-liquid smoke could give effect to arelatively open eggshells microstructure. It can be concluded that chitosan formulation with 20 g/l concentrationand 3% of liquid smoke concentration can be effective at 15 days curing time.